OUTCOMES OF THE COMBINED ANTEROPOSTERIOR APPROACH FOR FOREQUARTER AMPUTATION IN SHOULDER GIRDLE TUMORS. - Khan, Imran; Khan, Zeeshan; Ahmad, Israr; Khan, Arif; Saeed, Muhammad (Journal of Ayub Medical College Abbottabad, 2021)
Background: Forequarter amputation (FQA) is the surgical treatment of choice for tumours in the upper extremity and shoulder girdle that infiltrate the neurovascular bundle, shoulder joint and muscles of the shoulder girdle in non-salvageable cases. In both curative and palliative settings, FQA can serve as an effective oncological treatment for local control of tumour. Methods: All patients who underwent FQA in our unit from January 2016 till August 2019 for oncological indications were included in our study and their clinical outcomes were calculated. Results: Thirteen patients were included in the study including 8 male patients. Mean age of patients at surgery was 20 years (Range 10-53 years) with a minimum follow up of 6 months or till patient was deceased earlier. Six patients had primary osteosarcoma, 4 had Ewing's sarcoma, 2 had Spindle cell sarcoma while 1 had Giant cell tumour. Six patients underwent surgery with curative intent. No major per operative complication was encountered in any of the cases with a mean blood loss of 350 ml and mean duration of surgery being 75 minutes. At last, follow up only 6 patients were alive, with 2 patients alive with disease (Metastasis) and undergoing palliative treatment. None of our patients had local recurrence. Mean survivorship for the whole cohort was 9.2 months (Range 3-18 months) with a mean survivorship for the deceased group was 7.1 months (Range 3-16 months) and mean survivorship for alive patients was 11.6 months (range 9-18 months). All the alive patients had phantom limb sensations and only one had a prosthesis in place only for cosmetic reasons, at last follow up. Conclusion: Although FQA is a significantly body disfiguring procedure, but in large tumours of shoulder girdle, this is a viable option for local control of the disease. Based on our study, although relatively small sample size, we propose the combined anteroposterior approach to be safe and reliable for advanced shoulder girdle tumours.